PENGARUH YOGOAT (Yoghurt Susu Kambing) TERHADAP KEMAMPUAN FAGOSITOSIS MAKROFAG PERITONEAL TIKUS WISTAR MALNUTRISI - , YUNITA DEWI TRISNASARI; , dr. Endy P. Prawirohartono, Sp.A(K), MPH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: As many as 300 million toddlers in developing countries experience chronic malnutrition that causes 54% mortality of the total child mortality. Malnutrition and infections have a synergistic relationship. Malnutrition decreases body's immune response, declining number of cytokines, and macrophage dysfunction. Processing of milk into yogurt can provide a beneficial effect such as improving immunity. Objective: To determine the effect of goat milk yogurt (yogoat) on phagocytosis ability of malnourished Wistar rats. Methods: We conducted a randomized controlled trial (RCT) experimental study. A total of 28 Wistar rats aged 3 weeks with an average weight of 25-40 g were allocated into 4 groups i.e diet 100% + yogoat (SY)